2021
DOI: 10.1136/bmjpo-2021-001116
|View full text |Cite
|
Sign up to set email alerts
|

Working together better for mental health in children and young people during a pandemic: experiences from North Central London during the first wave of COVID-19

Abstract: Direct risk from infection from COVID-19 for children and young people (CYP) is low, but impact on services, education and mental health (so-called collateral damage) appears to have been more significant. In North Central London (NCL) during the first wave of the pandemic, in response to the needs and demands for adults with COVID-19, general paediatric wards in acute hospitals and some paediatric emergency departments were closed. Paediatric mental health services in NCL mental health services were reconfigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…1 , 47 studies were included in the systematic review (study characteristics are reported in Table 1 ). 32 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 Among these studies, 43 were included in the meta-analytical process, for a total of around 65 million subjects (suicides: 63,120,235; suicidal behaviors: 934,951; suicidal ideation: 156,234): two reporting rates of deaths for suicides, 48 , 50 26 reporting prevalence data about suicidal behaviors 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 <...…”
Section: Resultsmentioning
confidence: 99%
“…1 , 47 studies were included in the systematic review (study characteristics are reported in Table 1 ). 32 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 Among these studies, 43 were included in the meta-analytical process, for a total of around 65 million subjects (suicides: 63,120,235; suicidal behaviors: 934,951; suicidal ideation: 156,234): two reporting rates of deaths for suicides, 48 , 50 26 reporting prevalence data about suicidal behaviors 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 <...…”
Section: Resultsmentioning
confidence: 99%
“…Thus, implementing programs in schools should maximize accessibility for all students. A case study analysis in the United Kingdom of youth in wards (N=36) found that it was challenging to implement a youth mental health ward in a pediatric setting, which required setting up a new ward and combining physical health with mental health [ 27 ]. They also found that it required joint efforts in a multidisciplinary team setting involving nurses and pediatric psychiatrists, which led to adopting new leadership and managerial approaches as well as tailoring treatments to individual patients [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the articles explicitly described that the study was implemented during the COVID-19 pandemic in their titles [9,[19][20][21][22]24,[26][27][28]30,[32][33][34][35][36][37][38][39][40][41][42]44]. Others discussed their study relevance in relation to the COVID-19 pandemic in the abstract or main text [9,23,29,31,38,39].…”
Section: Covid-19 Contextmentioning
confidence: 99%
“…We planned to admit young people up to age 25 to reduce the burden on adult centres; this did not happen. But we did admit a wider than usual range of referrals from across the region and created a new ward for acute children and young people’s mental health admissions who would not previously have come to our hospital 18…”
Section: Methodsmentioning
confidence: 99%
“…But we did admit a wider than usual range of referrals from across the region and created a new ward for acute children and young people’s mental health admissions who would not previously have come to our hospital. 18 …”
Section: Methodsmentioning
confidence: 99%